Swimsuit [compact disc, unabridged] : a novel - Patterson, James, 1947- (Hachette Audio, 2009)
Supermodel Syd disappears while on a photo shoot in Hawaii. LA Times reporter Ben Hawkins is conducting his own research into the case, hoping to help the victim and get an idea for his next bestseller.